Dental Caries and its Conditioned Factors in Children from a Municipal Public School in Niterói, RJ, Brazil - Lívia Azeredo A. ANTUNES; Marcos Paulo Fonseca CORVINO; Leonardo dos Santos ANTUNES; Maria Bernadete Soares SORAGGI (Association of Support to Oral Health Research (APESB), 2007)
Purpose: To evaluate the manifestation of dental caries in 4-12-year-old schoolchildren from a municipal public school at the city of Niterói, RJ, Brazil, in the years 1990 and 2005, and to identify the most frequent feeding and oral hygiene habits among the children in 2005.Method: The study population comprised 370 individuals allocated into 3 groups: Group 1 (G1) with 150 4-12-year-old children of both genders that studied in the referred public school in 1990; Group 2 (G2) was similar to Group 1 but with children that studied in 2005; Group 3 (G3) composed of 70 parents/caregivers of G2 children, who answered a questionnaire arguing on feeding and oral hygiene habits. The mean DMF-T (decayed, missing and filled teeth) index, the statistical relationship as detected by Mann-Whitney nonparametric test and the percent frequencies for feeding and oral hygiene habits were calculated.Results: Dental caries was the most expressive value at both studied periods. However, there was decline in caries experience comparing 1990 and 2005 (p<0.05). There was no significant alteration in the number of missing and filled teeth between both periods (p>0.05). Regarding the feeding and oral hygiene habits, most children were bottle fed up to 1 year of age or a little longer, consumption of sugar-containing foods and drinks occurred 3 to 4 times a day, and the most frequent moment was between meals. In most children, toothbrushing started when the children already had several erupted teeth, the children themselves usually brushed their teeth with their own toothbrush and most of them did not use dental floss.Conclusion: Educational and preventive programs conducted at school are important and should be adjusted to the reality of each population because health is a relevant indicator of life quality.